(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются особенности метрополизация как доминантной тенденции территориальной организации общества в постсоветский период. Показана сопряжённость метрополизации с урбанизацией, регионализацией и глобализацией. Акцентирована активизация метрополизации в современной России, оценено влияние на метрополизацию фактора глобального финансово-экономического кризиса. Показано, что для трансформации крупного города (в том числе и регионального центра) в полномасштабную метрополию существенен комплекс взаимосвязанных факторов: размер и потенциал контролируемой территории, демографо-экономический масштаб самой метрополии, её структурные особенности, характер взаимодействия с другими метрополиями, в том числе и в рамках процесса глобализации. Выявлена специфика и детерминанты (периферийность, руральность, полиэтничность и др.) метрополизации на Юге России. METROPOLISATION AS A DOMINANT TENDENCY OF SPATIAL ORGANIZATION OF SOCIETY IN THE POST-SOVIET PERIOD: UNIVERSAL DISPLAYS AND SOUTH-RUSSIAN SPECIFICITY The features of metropolisation as a dominant tendency of spatial organization of society in the post-soviet period are considered. Association of metropolisation with urbanization, regionalization and globalization is shown. Activization of metropolisation in the modern Russia is emphasized, an impact on metropolisation the factor of global financial and economic crisis is estimated. It is shown that for the transformation of large city (including regional center) to the full-scale metropolis the complex of interrelated factors: size and potential of controlled territory, demographic-economic scale of the metropolis itself, its structural features, pattern of interaction with other metropolises, also within the process of globalization is essential. Specificity and determinants (peripheracy, rurality and polyethnicity, etc) of metropolisation in the South Russia are revealed.